Cholecystectomy and post-cholecystectomy suffering - Varela López, J A; Peri, L (Cirugía del Uruguay, 2020)
1) Conditions ansmg as a result of cholecystectomis should be regarded as an important chapter in patholo.gy, comprising every' disease clinically manifest asan involvement of the doudeno-biliary junction. 2} A discussion is carried out of the various designations proposed for the symptoms persisting after the cholecystectomy and of the conceptual confusion caused by sorne of them. 3) From studies conducted by other authors and by ourselves it may · be inferred that: a) Most of the poor results of cholecystectomies on functioning gallbladders are due solely to the higher frequency of cases where they are erroneously blamed for the involvement. In non-functioning gall-bladders the frequency of such error is lower. b) Neither does the percentage. of good or poor results depend upon the presence or absence of gallstones but on the percentage of error in the indication of surgery, which is higher in cholecystopathies without stones. The patient's fate is closely dependant on a thorough understanding of every feature of the disease. 4 It has been demonstrated that the true sequelae of cholecystectomies are of rare oc.currence and are confined to three fac. ors namely, immediate post-opera ti ve cliarrhea due to atony of Oddi's sphincter, :g)l hypochondrium involvement owing to duodenal bend arising from gallbladder bed adbesions and the affliction originat:i ng in an amputation neuroma. 5 A survey is carried out of therapeutic ·errors resulting in the persistence of symptoms following gallbladder surgery, attention being drawn to the important role played by an insufficient understanding of frequent neurotic disorders.